Pengaruh Ukuran Perusahaan, Kinerja Lingkungan, dan Voluntary Disclosure terhadap Nilai Perusahaan: Studi Empiris Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia - Natashia Avelyn; Efrizal Syofyan (Universitas Negeri Padang, 2023)
This study aims to provide empirical evidence regarding the effect of firm size, environmental performance, and voluntary disclosure partially and simultaneously on firm value in basic and chemical industrial companies. This study uses a type of causal research with a quantitative approach. The population in this study is the basic and chemical industrial sector companies listed on the Indonesia Stock Exchange in 2014 - 2020 as many as 80 companies. This study used a purposive sampling technique with a selected sample of 16 companies. This study uses secondary data obtained from www.idx.co.id and company sites. The data analysis method used is panel data regression analysis. The measurement of firm value follows the latest Tobin's Q measurement by comparing the market value of equity with the book value of equity. The results showed that the variables of firm size, environmental performance, and voluntary disclosure simultaneously had no effect on firm value. Based on the partial test, firm size and environmental performance variables have no effect on firm value with a negative relationship direction and voluntary disclosure variables have a significant negative effect on firm value. For further research, it is recommended to use other variables and expand the research sample.